Mediating role of perceived social support in the relationship between perceived stress and job burnout among midwives in the post‐COVID‐19 era - Cuiping Liu; Chongyu Yue; Lei Liu; Ting Liu; Xuelei Wang; Yan Hou; Shaobo Gao (Wiley, 2023)
Abstract Aim The aim of this study was to explore the mediating role of perceived social support in the association between perceived stress and job burnout in midwives. Design A descriptive, cross‐sectional online survey. Methods Using the stratified cluster sampling method, 329 midwives in 20 hospitals in China were selected as the participants. They completed self‐report assessment measures of job burnout, perceived stress and perceived social support. Results 63.5% of the participants had job burnout. Perceived stress was negatively associated with social support (r = −.350, p < .01), while it was positively associated with job burnout (r = −.382, p < .01). Social support was negatively correlated with job burnout (r = −.569, p < .01). The total effect of perceived stress on job burnout was 0.474 (95% CI: 0.367 ~ 0.596, p < .01), the direct effect was 0.242 (95% CI: 0.142 ~ 0.355, p < .01), and the indirect effect was 0.232 (95% CI: 0.160 ~ 0.316, p < .01). Social support programmes for midwives should be implemented to control the impact of perceived stress on job burnout.